REASONS FOR CONTINUATION OR CESSATION OF INDIAN T IUDS (PREGNA) AFTER 21 MONTHS OF PLACEMENT - Z. Shahvary; M. Allamy; SH. Shokraby; H. Hghani (Iran University of Medical Sciences, 2004)
Nowadays IUDs are the most commonly used reversible contraceptives in the world While more than 130 million women are thaught to use IUDs worldwide, a-large number of the users put it away for some medical reason, anyhow, side effects of this device will diminish with precise patient's screening programs. Determining the efficacy of use in unitentional pregnancies and also the side effects after 21 months indian T IUDs placement, we conducted a historical cohort retrospectiove study, in which 1008 medical record, belonged to all women whom had reffered to an urban health center were reviewed. The results showed that the probability of continuation with this type of IUDs at the end of 21 months of use was 0.6% and after this time 300 women had discontinued the use of it their main reasons were expulsion 8.3% bleeding and pain 9.5% and cessation due to increased lentgh 2.5%. Besides 6% of porticipants had requested requosted to put it away because of some personal reasons. To conclude, the results were the some as other similar researches, most side effects had occurred during the first year of placement, and as the time passed the side effects started to deminish. We recommend a similar study to investigate the side effects after 21th months of placement.